Enrichment of fetal and maternal long cell‐free DNA fragments from maternal plasma following DNA repair. (10th January 2019) - Vong, Joaquim S.L.; Jiang, Peiyong; Cheng, Suk‐Hang; Lee, Wing‐Shan; Tsang, Jason C.H.; Leung, Tak‐Yeung; Chan, K.C. Allen; Chiu, Rossa W.K.; Lo, Y.M. Dennis
Abstract: Objective: Cell‐free DNA (cfDNA) fragments in maternal plasma contain DNA damage and may negatively impact the sensitivity of noninvasive prenatal testing (NIPT). However, some of these DNA damages are potentially reparable. We aimed to recover these damaged cfDNA molecules using PreCR DNA repair mix. Methods: cfDNA was extracted from 20 maternal plasma samples and was repaired and sequenced by the Illumina platform. Size profiles and fetal DNA fraction changes of repaired samples were characterized. Targeted sequencing of chromosome Y sequences was used to enrich fetal cfDNA molecules following repair. Single‐molecule real‐time (SMRT) sequencing platform was employed to characterize long (>250 bp) cfDNA molecules. NIPT of five trisomy 21 samples was performed. Results: Size profiles of repaired libraries were altered, with significantly increased long (>250 bp) cfDNA molecules. Single nucleotide polymorphism (SNP)‐based analyses showed that both fetal‐ and maternal‐derived cfDNA molecules were enriched by the repair. Fetal DNA fractions in maternal plasma showed a small but consistent (4.8%) increase, which were contributed by a higher increment of long fetal cfDNA molecules. z ‐score values were improved in NIPT of all trisomy 21 samples. Conclusion: Plasma DNA repair recovers and enriches long cfDNA molecules of both fetal and maternal origins in maternal plasma. Abstract : What is already known about this topic? Most of the cell‐free DNA (cfDNA) fragments in maternal plasma have sizes less than 200 bp, with fetal molecules being shorter than maternal ones. DNA damages exist in cfDNA, particularly single‐strand nicks. Occasional no call for noninvasive prenatal testing (NIPT) can be caused by insufficient fetal DNA fraction. What does this study add? Repair of cfDNA by PreCR repair mix can recover a subset of long (>250 bp) cfDNA molecules. Both fetal and maternal long cfDNA are enriched by PreCR repair treatment. Mild but consistent increments in fetal DNA fractions after PreCR repair, which are contributed by higher enrichment of long fetal cfDNA molecules. PreCR repair treatment improves NIPT of trisomy 21 by elevating z scores resulting in better discrimination of aneuploid from euploid samples.